Deletion of the RNA-binding proteins Zfp36l1 and Zfp36l2 leads to perturbed thymic development and T-lymphoblastic leukaemia - Hodson, Daniel J. (2010)
ZFP36L1 and ZFP36L2 are RNA-binding proteins (RBPs) which interact with AU-rich elements in the 3'UTR of mRNA, leading to mRNA degradation and translational repression. Mice lacking ZFP36L1 and ZFP36L2 during thymopoiesis develop a Notch1-dependent T cell acute lymphoblastic leukaemia (T-ALL). Prior to the onset of T-ALL, thymic development is perturbed with accumulation of cells which have passed through the β-selection checkpoint without first expressing T cell receptor β (TCR-β). Notch1 expression is increased in non-transformed thymocytes in the absence of ZFP36L1 and ZFP36L2. Both RBPs interact with evolutionarily conserved AU-rich elements within the 3' untranslated region of Notch1 and suppress its expression. These data establish a role for ZFP36L1 and ZFP36L2 during thymocyte development and in the prevention of malignant transformation.